Effect of self-discrepancy on functioning : role of cause attribution as moderator - Tan, Yan Ling (Nanyang Technological University, 2021)
Self-discrepancy occurs when individuals perceive a gap between their actual self, who they think they are currently, and either their ideal or ought self-representation. Self- representations can be evaluated from a personal standpoint and from the standpoint of a close other. The discrepancy between individuals’ actual self and their self-representations from the two standpoints are labelled as personal and relational self-discrepancy. High perceived personal self-discrepancy in an individual is often associated with poorer emotional and psychological wellbeing. However, little is known about the implication of personal self- discrepancy on relational well-being as well as the relationship between relational self- discrepancy and wellbeing. This research investigated how both personal and relational self- discrepancy might be related to personal and relational functioning. Additionally, this research also examined the moderating effects of cause attribution (i.e. whether individuals perceive their self-discrepancy as due to person-self, situation or interpersonal causes) in the relationship between self-discrepancy and functioning. Undergraduates in Singapore (N = 227; SD = 21.00) were recruited to complete an online questionnaire pertaining to their personal and relational self-discrepancy, cause attribution of the discrepancy, and personal and relational functioning. Regression analyses showed that both personal and relational self- discrepancy negatively predicted personal functioning, whereas only relational self- discrepancy negatively predicted relational functioning. Interpersonal cause attribution was also found to significantly moderate the relationship between relational self-discrepancy and relational functioning, such that the relationship is stronger at higher levels of interpersonal cause attribution. Implications and directions for future research were discussed.